2017
DOI: 10.1039/c6cc09933e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical probing of thiotetronate bio-assembly

Abstract: Chemical 'chain termination' probes were utilised for the investigation of thiotetronate antibiotic biosynthesis in the filamentous bacteria Lentzea sp. and Streptomyces thiolactonus NRRL 15439. The use of these tools led to the capture of biosynthetic intermediates involved in the thiotetronate polyketide backbone assembly, providing first insights into substrate specificity and in vivo intermediate processing by unusual iterative synthases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The malonyl and methylmalonyl carba(dethio)- N -acetylcysteamine probes 81 and 83 have now been used to study a multitude of PKS systems in vitro and in vivo including the prototypical 6-deoxyerythonolide (DEBS) PKS, 128 the polyether Lasalocid (LAS) PKS, 129 the iterative partially reducing (PR) PKSs involved in the syntheses of 6-methylsalicylate and 6-pentylsalicylate (6-MSAS), 130, 131 and the thiotetronate PKS responsible for thiolactomycin biosythesis. 132, 133 A representative metabolite from in vivo feeding studies of the lasalocid PKS system is shown in Fig. 24 highlighting the useful information that one can obtain from this analysis, which in the case of lasalocid revealed the timing of ring formation in this polyether antibiotic.…”
Section: Chemical Tools To Interrogate Pks Enzymesmentioning
confidence: 99%
“…The malonyl and methylmalonyl carba(dethio)- N -acetylcysteamine probes 81 and 83 have now been used to study a multitude of PKS systems in vitro and in vivo including the prototypical 6-deoxyerythonolide (DEBS) PKS, 128 the polyether Lasalocid (LAS) PKS, 129 the iterative partially reducing (PR) PKSs involved in the syntheses of 6-methylsalicylate and 6-pentylsalicylate (6-MSAS), 130, 131 and the thiotetronate PKS responsible for thiolactomycin biosythesis. 132, 133 A representative metabolite from in vivo feeding studies of the lasalocid PKS system is shown in Fig. 24 highlighting the useful information that one can obtain from this analysis, which in the case of lasalocid revealed the timing of ring formation in this polyether antibiotic.…”
Section: Chemical Tools To Interrogate Pks Enzymesmentioning
confidence: 99%
“…In an effort to confirm the proposed noncolinear arrangement of modules in alpiniamide biosynthesis, and to investigate whether the alpiniamide backbone might be synthesized as two separate chains, we tested malonyl- and methylmalonyl-mimic probes (chain terminators) in feeding experiments to offload and detect enzyme-bound intermediates from the assembly line(s) in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces M1146_RSalp was grown in the presence of either of the chemical probes 2 and 3 (Figure ), mimics, respectively, of the extender units malonyl- and methylmalonyl-CoA. The method relies upon successful competition by the mimic for condensation with the growing chain, and offloading of shorter chains is generally found to be more effective. A summary of the intermediates intercepted in vivo and detected by LC-HRMS analyses is given in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations